2020
DOI: 10.1111/imj.14641
|View full text |Cite
|
Sign up to set email alerts
|

Review of HIV testing recommendations in Australian specialty guidelines for HIV indicator conditions: a missed opportunity for recommending testing?

Abstract: Background Australian National human immunodeficiency virus (HIV) Testing policy recommends HIV indicator condition‐based testing, adapted from the European AIDS Clinical Society (EACS) guidelines. Aim To evaluate the extent that Australian non‐HIV specialty guidelines mention and recommend HIV testing in HIV indicator conditions. Methods EACS guidelines were reviewed to produce a list of 24 AIDS‐defining conditions (ADC) and 31 indicator conditions (IC) where HIV prevalence >0.1%, and 5 IC where HIV non‐diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Multiple barriers to testing have been identified including lack of knowledge of IC, lack of guidelines, low‐risk perception and perceived lack of knowledge around HIV . Studies reviewing non‐HIV specialty guidelines for IC found that many of these guidelines do not consider HIV testing as part of the investigations for IC . Thus, specialist clinicians managing IC may not be aware of the prevalence of undiagnosed HIV among their patients with such conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple barriers to testing have been identified including lack of knowledge of IC, lack of guidelines, low‐risk perception and perceived lack of knowledge around HIV . Studies reviewing non‐HIV specialty guidelines for IC found that many of these guidelines do not consider HIV testing as part of the investigations for IC . Thus, specialist clinicians managing IC may not be aware of the prevalence of undiagnosed HIV among their patients with such conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6,13,16 Studies reviewing non-HIV specialty guidelines for IC found that many of these guidelines do not consider HIV testing as part of the investigations for IC. 10,17,18 Thus, specialist clinicians managing IC may not be aware of the prevalence of undiagnosed HIV among their patients with such conditions. This study aimed to determine whether patients with an IC admitted to an acute General Medicine Unit (GMU) at a tertiary centre were being tested for HIV and to evaluate the effectiveness of an educational intervention focused on HIV testing recommendations to improve testing rates.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, interestingly, there is no specific suggestion within some guidelines to test for HIV in those with IPD 3,12 . This could additionally be embedded in other Australian specialty guidelines 13 …”
Section: Discussionmentioning
confidence: 99%
“…Many of the reviews of late diagnoses find multiple missed opportunities for testing prior to the positive test – potentially allowing treatment when immune status was still relatively normal. Two papers in this issue of the Internal Medicine Journal address the issue of HIV testing in other diseases that, while not AIDS‐defining, may be associated with HIV infection . Lin and colleagues review Australian specialty guidelines for these indicator conditions and find room for improvement in the recommendations around HIV testing.…”
mentioning
confidence: 99%
“…Two papers in this issue of the Internal Medicine Journal address the issue of HIV testing in other diseases that, while not AIDS‐defining, may be associated with HIV infection . Lin and colleagues review Australian specialty guidelines for these indicator conditions and find room for improvement in the recommendations around HIV testing. The second paper by King and colleagues finds that a simple educational intervention is effective at increasing the rate of HIV testing in a general medical unit, but that rates of testing are still far too low, and calls for new strategies to boost these low testing rates.…”
mentioning
confidence: 99%